Introduction to chemical engineering - Land, C.M. van't (Hoboken, New Jersey : John Wiley & Sons, Inc., 2024)
'Chemical engineering is a skill and profession with applications in many industries, including chemical manufacturing, oil and gas refining and processing, food processing, biofuels, pharmaceutical manufacturing, plastics production and use, and new energy recovery and generation technologies. Most of the processes in the industries are typically designed by chemical engineers. However, the people who operate these facilities, sell the products produced by these plants, those who have overall business management responsibilities, and those who interface with chemical engineers in product discovery/development area, can be other types of engineers (mechanical, civil, electrical, software and computer, safety), or scientists such as chemists, biologists, physicists etc. Some of these engineers and scientists might work as operating technicians depending on their level of education. In addition, there are businesses and marketing majors who work in chemical plants. All of these individuals potentially have gaps in their chemical engineering knowledge that could benefit from applied knowledge relating to the chemical engineering discipline.'--
Includes bibliographical references and index.
Keywords: Chemical engineering; Chemical engineering -- Textbooks